Graphite material and manufacturing method and application thereof
By heating graphite raw materials in the presence of oxidation process gas to prepare graphite materials with specific properties, the problems of low oxidation degree and high resistance of existing graphite materials are solved, and performance optimization and safety improvement in electrochemical systems are achieved.
Patent Information
- Application Number
- CN202380041741.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-25
- Filing Date
- 2023-04-13
- Publication Date
- 2024-12-31
AI Technical Summary
Existing graphite materials are prone to low oxidation and high resistance in electrochemical systems, resulting in functional losses and safety risks, and have poor conductivity, making it difficult to balance between low oxidation and low resistance.
By selecting the appropriate graphite feedstock and heating to 300-1700°C in the presence of an oxidation process gas, the process parameters are controlled to prepare a intensity ratio of 0.11 g/cm3 with a pH of at least 5.4, a Scott density of less than or equal to 0.11 g/cm3 and a Raman D/G Graphite material from 0.220 to 0.420.
Achieve the optimal balance between low oxidation and low resistance of graphite materials, extend battery life, slow down efficiency, reduce the risk of graphite decomposition into gases, improve safety, and allow less conductivity to be used Additives to achieve higher battery capacity.
Smart Images

Figure BDA0005143737200000141 
Figure BDA0005143737200000161 
Figure BDA0005143737200000181
Abstract
Description
Technical Field
[0001] The present invention relates to a graphite material having a favorable balance between low oxidation susceptibility and low electrical resistance, and to a method for producing such a graphite material and to uses of the graphite material. Background Art
[0002] Carbon conductive additives are used in various primary and secondary batteries, such as alkaline zinc / manganese dioxide batteries, zinc-carbon batteries, lithium primary and rechargeable batteries, nickel-cadmium batteries, lead-acid batteries, nickel-metal hydride batteries, lithium-sulfur batteries, lithium-air batteries, metal-air batteries with metals such as zinc or iron, fuel cells, and capacitor systems.
[0003] Conductive additives are applied to the electrodes of electrochemical cells to reduce electrode resistance. Carbonaceous powder materials are generally selected as conductive additives due to their light weight and inertness to acidic and alkaline electrolytes. Conductive additives generally do not contribute to the electrochemical process of the electrode, which means that for the high energy density of the battery, the amount of conductive additive applied is ideally minimized. The general carbon conductive additives used are fine graphite powder and conductive carbon black (see, for example, M.E. Spahr, Lithium-ion Batteries-Science and Technology, M.Yoshio, R.J. Brodd, A.Kozawa (Eds.), Springer, New York, 2009, Chapter 5).
[0004] Graphite is the most common allotrope of carbon and is characterized by good electrical, thermal and lubricity properties. Graphite is widely used as a conductive additive in the above-mentioned battery and fuel cell applications due to its good electrical conductivity, low density and generally excellent chemical inertness.
[0005] Lithium-ion batteries are used for both consumer and industrial purposes. Lithium-ion batteries are usually composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode active material to be used is natural or synthetic graphite. 2 ), manganese spinel (LiMn 2 O 4 ) and other materials are mainly used as the active material of the positive electrode. Since the positive electrode active material has high resistance, the resistance of the positive electrode is reduced by using a carbon-based conductive additive.
[0006] Lead-acid batteries are used for consumer and industrial purposes. Lead-acid batteries are generally composed of a positive electrode, a negative electrode, an electrolyte, and a separator. A small amount of conductive carbon is added to the negative electrode of the lead-acid battery to improve the cycle life and charge acceptance of the battery when operating in a high rate partial state of charge (HRPSoC) mode, such as used in hybrid electric vehicles (see, for example, K. Nakamura, M. Shiomi, K. Takahashi, M. Tsubota, Journal of Power Sources 59 (1996) 153; M. Shiomi, T. Funato, K. Nakamura, K. Takahashi, M. Tsubota, Journal of Power Sources, 64 (1997), 147; and D. Pavlov, P. Nikolov, T. Rogachev, Journal of Power Sources 196 (2011), 5155-5167).
[0007] Alkaline batteries are used for consumer and industrial purposes. Typically, a primary alkaline battery comprises an anode, a cathode, a separator permeable to an electrolyte between the anode and the cathode, and an alkaline electrolyte, usually consisting of an aqueous solution of potassium hydroxide, contacting the anode and the cathode. The cathode active material comprises manganese dioxide or nickel oxyhydroxide or a mixture thereof, and a conductive additive (e.g., graphite) to increase the conductivity of the cathode. The cathode material in an alkaline battery is manganese dioxide (EMD, electrolytic manganese dioxide).
[0008] Fuel cells are used for industrial purposes. Fuel cells are usually composed of a membrane, a catalyst layer, a gas diffusion layer, a microporous layer, and a bipolar plate. The bipolar plate is usually produced by molding a highly conductive graphite-polymer composite. The graphite must have high conductivity and also be resistant to oxidation (especially in the cathode where oxygen is in direct contact with the bipolar plate). In addition, the gas diffusion layer and the microporous layer are in direct contact with oxygen and must be conductive. The use of highly conductive graphite with high oxidation resistance can improve the performance of the fuel cell system.
[0009] One of the drawbacks of using graphite materials as conductive additives is their limited stability to oxidative environments, especially under the harsh conditions found in electrochemical systems. When used as a conductive additive, oxidation of the surface of the graphite material can lead to lower conductivity of the powder. In addition, the loss of graphite during oxidation will result in a loss of functionality in the system. Furthermore, further increases in oxidation will lead to the release of gases such as CO or CO 2 Large quantities of this can result in potentially dangerous degradation of systems in which graphite is used.
[0010] Therefore, low oxidation susceptibility is an important characteristic of graphite materials in such applications.
[0011] As discussed in 7,273,680 B2, it is believed that the oxidation resistance of a particular graphite is related to the specific surface area of the graphite particles, whereby the smaller the surface area, the greater the oxidation resistance of the graphite. This document teaches that oxidation resistant graphite can be produced by heat treating high purity synthetic or natural graphite at high temperatures, such as greater than 2500°C or greater than 3000°C in an inert atmosphere.
[0012] In the application of graphite materials as conductive additives, the resistance of the material is another very important parameter. Resistance is a material property related to the degree of resistance of the material to electric current. Materials with low resistivity are materials that easily conduct electric current.
[0013] Purpose of the Invention
[0014] The object of the present invention is to provide a novel graphite material having superior properties compared to the graphite materials of the prior art. In particular, the present invention aims to provide a graphite material having an improved balance between low susceptibility to oxidation and low electrical resistance and products comprising these graphite materials.
[0015] Another object of the present invention is to provide a suitable process for producing such graphite materials. Summary of the invention
[0016] The present inventors have unexpectedly discovered that by selecting suitable graphite raw materials and carefully controlling process parameters, graphite materials with excellent properties can be prepared. In particular, the present inventors have unexpectedly discovered that an optimal balance between low oxidation susceptibility and low electrical resistance can be achieved by graphite materials having the following properties: pH of at least 5.4; Scott density less than or equal to 0.11 g / cm 3 ; and a Raman D / G intensity ratio of 0.220 to 0.420 when measured with a laser having an excitation wavelength of 632.8 nm.
[0017] Furthermore, the present invention provides a method for producing a graphite material, wherein a) a graphite starting material is subjected to a surface modification process, said surface modification process comprising heating to a temperature of 300-1700° C. in the presence of an oxidizing process gas, such as but not limited to oxygen, air, oxygen-enriched air, carbon dioxide, ozone, steam, NO x (For example, but not limited to NO 2 、NO、N 2 O) or any combination thereof; and b) obtaining the graphite material described herein.
[0018] The present invention also relates to a negative electrode or a positive electrode comprised in a battery, comprising the graphite material described herein, preferably as a conductive additive.
[0019] The present invention also relates to a battery comprising the graphite material described herein, wherein the battery is preferably a lithium-ion battery, a lead-acid battery, an alkaline battery or a nickel-cadmium battery.
[0020] The present invention also relates to a fuel cell comprising the graphite material described herein.
[0021] Furthermore, the present invention relates to the use of the graphite material described herein in any of the following: lithium ion batteries, lead acid batteries, alkaline batteries, nickel cadmium batteries, fuel cells.
[0022] The graphite material of the present invention can be advantageously used in batteries or fuel cells. The use of graphite materials with low oxidation ease and low resistance has the benefits of extending the life of batteries or fuel cells, slowing down the reduction in efficiency of batteries or fuel cells, and improving safety by reducing the risk of graphite decomposition into gas. In addition, lower resistance allows the use of less conductive additives in batteries or fuel cells, thereby achieving higher battery capacity. DETAILED DESCRIPTION
[0023] definition
[0024] In the context of the present invention, the term "resistance", ρ, sometimes also called resistivity, volume resistivity or specific resistivity, is a material property related to the degree of resistance of a material to electric current, expressed in SI units Ohm / m or Ohm / cm (Ω / m or Ω / cm, respectively).
[0025] Volume resistivity can be measured by the following method:
[0026] preparing a mixture containing 95% electrolytic manganese dioxide and 5% by weight of graphite (when synthetic or natural graphite is used as the graphite starting material) or 3% by weight of graphite and 97% electrolytic manganese dioxide (when expanded graphite is used as the graphite starting material);
[0027] 10 g of the resulting mixture was pressed at 180 Nm in a mold having a length of 50 mm and a width of 12 mm to obtain a block;
[0028] Measure the height (H) and width (W) of the block;
[0029] Measure bulk resistance (R) using a 4-point probe.
[0030] • Calculate the resistivity as H*R / D, where D is the distance of the probe measuring needle.
[0031] Low resistivity materials are materials that easily conduct electrical current.
[0032] In the context of the present invention, the term "oxidability" refers to the resistance of a material to oxidation. It is measured by ripening the material in a KOH aqueous solution and measuring the absorbance of the solution. In particular, the oxidability of a graphite material can be measured by a method comprising the following steps:
[0033] a) preparing a mixture of 40 wt % of a graphite material and 60 wt % of electrolytic manganese dioxide;
[0034] b) The mixture of step a) was pressed together and 6.8 metric tons / cm 2 The pressure is 5 seconds to form a tablet,
[0035] c) aging the tablets at 60° C. in 20 mL of a 30 wt % KOH aqueous solution to obtain an aging solution;
[0036] d) filtering the slaking solution to obtain a filtered slaking solution;
[0037] e) measuring the absorbance at 410 nm using a UV-Vis spectrometer; and
[0038] f) The susceptibility to oxidation of the tested graphite material is evaluated by measuring the absorbance value.
[0039] The oxidation ease is defined as the measured absorbance value. The lower the measured absorbance, the lower the oxidation ease and the higher the oxidation resistance of the graphite material.
[0040] In the context of the present invention, the term "conductive additive" refers to a material applied to an electrode of an electrochemical cell to reduce electrode resistance. Carbonaceous powder materials are generally selected as conductive additives due to their light weight and inertness to acidic and alkaline electrolytes. Conductive additives generally do not contribute to the electrochemical process of the electrode, which means that for the high energy density of the battery, the amount of conductive additive applied is ideally minimized. The general carbon conductive additives used are fine graphite powder and conductive carbon black (see, for example, M. E. Spahr, Lithium-ion Batteries-Science and Technology, M. Yoshio, R. J. Brodd, A. Kozawa (Eds.), Springer, New York, 2009, Chapter 5).
[0041] The graphite material of the present invention and its properties are described in more detail below. All explanations also apply to other aspects of the present invention, such as the method of the present invention, the positive electrode or negative electrode contained in the battery containing the graphite material, the battery or fuel cell containing the graphite material and the use of the graphite material.
[0042] Graphite materials
[0043] In a first aspect, the present invention provides a graphite material having the following properties:
[0044] a) a pH of at least 5.4, measured as described herein;
[0045] b) a Scott density less than or equal to 0.11 g / cm 3 ;as well as
[0046] c) When measured with a laser having an excitation wavelength of 632.8 nm, the Raman D / G intensity ratio is 0.220 to 0.420.
[0047] The pH of the graphite material of the present invention is at least 5.4, preferably a pH of 5.4-12, or 5.4-11, or 5.4-10. The pH of the graphite material can be measured by dispersing the material in water and measuring the pH using a pH meter. Any reference to the pH of the graphite material in this specification relates to the pH of the dispersion of the graphite material in water.
[0048] In addition, the Scott density of the graphite material of the present invention is less than or equal to 0.11 g / cm 3 , preferably less than or equal to 0.10 g / cm 3 , or less than or equal to 0.09g / cm 3 The Scott density can be 0.001 to 0.11 g / cm 3 , preferably 0.01 to 0.10 g / cm 3 or 0.01 to 0.09 g / cm 3 In a preferred embodiment, the Scott density is 0.03 to 0.11 g / cm 3 , for example 0.03 to 0.10 g / cm 3 or 0.03 to 0.09 g / cm 3 The Scott density can be measured using a Scott volume meter according to ASTM B 329-98 (2003).
[0049] In addition, when measured with a laser having an excitation wavelength of 632.8 nm, the Raman D / G intensity ratio of the graphite material of the present invention is 0.220 to 0.420, for example 0.230 to 0.420 or 0.220 to 0.400. In a preferred embodiment, the Raman D / G intensity ratio of the graphite material of the present invention is 0.230 to 0.400. The Raman D / G intensity ratio is based on the intensity ratio of the so-called spectral band D and spectral band G. These peaks are characteristic of carbon materials and are located at 1350 cm -1 and 1580cm -1 Measured at.
[0050] It will also be appreciated that the graphite material may also be defined by each pH value range, independently of or in addition to each Scott density value range and Raman D / G intensity ratio range (obviously provided that they are not mutually exclusive).
[0051] The graphite material of the present invention may have a pH of 5.4-12, a 3 The Scott density is 0.170 and the Raman D / G intensity ratio is 0.220 to 0.420.
[0052] In a preferred embodiment of the present invention, the graphite material has a pH of 5.4-11, a 3 The Scott density is between 0.220 and 0.400 for the Raman D / G intensity ratio.
[0053] In a preferred embodiment of the present invention, the graphite material has a pH of 5.4-11, a 3 The Scott density is between 0.230 and 0.400 for the Raman D / G intensity ratio.
[0054] In a preferred embodiment of the present invention, the graphite material has a pH of 5.4-10, a 3 The Scott density is between 0.230 and 0.400 for the Raman D / G intensity ratio.
[0055] In some embodiments, the graphite material of the present invention is also characterized by a specific particle size distribution. The particle size distribution can be measured using laser diffraction. The particle size distribution is generally defined by the values D10, D50, and D90, wherein 10% (by volume) of the particle population has a size below the D10 value, 50% (by volume) of the particle population has a size below the D50 value, and 90% (by volume) of the particle population has a size below the D90 value.
[0056] The D90 of the graphite material of the present invention may be at least 5 μm, or at least 6 μm, or at least 7 μm, or at least 11.0 μm, preferably at least 12 μm or at least 13 μm. The D90 of the graphite material of the present invention may be 11 to 120 μm, or 12 to 120 μm, or 13 to 120 μm. In certain embodiments in which a non-expanded graphite material is used as the starting material, D90 values of 11 to 50 μm, or 11 to 40 μm, or 11 to 30 μm are preferred.
[0057] Likewise, in some embodiments, the particle size distribution value D50 will be from 1 to 50 μm, although in certain embodiments where non-expanded graphite material is used as the starting material, D50 values of 5 to 20 μm or 6 to 15 μm are preferred.
[0058] It will also be appreciated that the graphite material may also be defined by each D90 value range, independently of or in addition to the D50 value range (obviously provided that they are not mutually exclusive).
[0059] In some embodiments where a non-expanded graphite material is used as the starting material, the graphite material has a D90 value of 11 to 50 μm and a D50 value of 5 to 20 μm.
[0060] For certain embodiments, the graphite material of the present invention is further characterized by an oxygen concentration of at least 0.042 wt % based on the total weight of the graphite material. In preferred embodiments, the oxygen concentration is 0.042-1.0 wt %, or 0.042-0.9 wt %, or 0.042-0.7 wt %, or 0.042-0.6 wt %, or 0.042-0.5 wt %. The oxygen concentration can be measured by elemental analysis to measure the elemental oxygen content of the graphite material. The oxygen concentration corresponds to the oxygen content of the graphite material.
[0061] In a preferred embodiment of the present invention, the graphite material has a D90 of at least 11.0 μm and an oxygen concentration of at least 0.042 wt %, based on the total weight of the graphite material.
[0062] In a preferred embodiment of the present invention, the graphite material of the present invention has a D90 of 11 to 120 μm, a D50 of 1 to 50 μm, and an oxygen concentration of 0.042 to 1.0 wt %, based on the total weight of the graphite material.
[0063] In a preferred embodiment, the graphite material has a pH of 5.4 to 11, a pH of 0.03 to 0.11 g / cm 3 The material has a Scott density of 0.220 to 0.400, a Raman D / G intensity ratio of 12 to 120 μm, and an oxygen concentration of 0.042 to 1.0 wt %.
[0064] In a preferred embodiment, the graphite material has a pH of 5.4 to 11, a pH of 0.03 to 0.10 g / cm 3 The Scott density is 0.042 to 0.6 wt % and the Raman D / G intensity ratio is 0.230 to 0.400. The D90 is 13 to 120 μm and the oxygen concentration is 0.042 to 0.6 wt %.
[0065] In a preferred embodiment, the graphite material has a pH of 5.4 to 10, a pH of 0.03 to 0.09 g / cm 3 The Scott density is 0.042 to 0.6 wt % and the Raman D / G intensity ratio is 0.230 to 0.400. The D90 is 13 to 120 μm and the oxygen concentration is 0.042 to 0.6 wt %.
[0066] The graphite material of the present invention is also characterized by at least 5.5 m 2 The BET surface area can be measured based on the procedure proposed by Brunauer, Emmet and Teller (Adsorption of Gases in Multimolecular Layers, J. Am. Chem. Soc., 1938, 60, 309-S1 9).
[0067] The ash content may be less than 0.3 wt %, preferably less than 0.2 wt %, more preferably less than 0.1 wt %, even more preferably less than 0.08 wt %, still more preferably less than 0.06 wt %, for example less than 0.05 wt %, most preferably less than 0.04 wt %. The ash content may be measured according to ASTM C561.
[0068] The graphite material of the present invention may have an oxidation ease of less than or equal to 0.19 and an electrical resistance of less than or equal to 600 mΩ·cm, preferably less than or equal to 400 mΩ·cm, and most preferably less than or equal to 285 mΩ·cm.
[0069] The graphite material may preferably have an oxidation ease of less than or equal to 0.18 or 0.17 or 0.16 or 0.15.
[0070] The oxidizability is defined as the absorbance value (absorbance intensity ratio) measured by a method comprising the following steps:
[0071] a) preparing a mixture of 40 wt % of a graphite material and 60 wt % of electrolytic manganese dioxide;
[0072] b) The mixture of step a) was pressed together and 6.8 metric tons / cm 2 The pressure is 5 seconds to form a tablet,
[0073] c) aging the tablets at 60° C. in 20 mL of a 30 wt % KOH aqueous solution to obtain an aging solution;
[0074] d) filtering the slaking solution to obtain a filtered slaking solution;
[0075] e) measuring the absorbance of the filtered aging solution at 410 nm using a UV-Vis spectrometer; and
[0076] f) The susceptibility to oxidation of the tested graphite material is evaluated by measuring the absorbance value.
[0077] In addition, the electrical resistance of the graphite material is less than or equal to 260 mΩ·cm, or less than or equal to 255 mΩ·cm, or less than or equal to 250 mΩ·cm.
[0078] In general, the graphite material of the present invention characterized by the parameters given above can be obtained by subjecting a graphite starting material to a process comprising the following steps: x (including but not limited to NO 2 、NO、N 2 O) or any combination thereof) to a temperature of 300°C to 1700°C, preferably 500°C to 1400°C, most preferably 700°C to 1100°C.
[0079] The graphite material of the present invention can be prepared by the method described in detail below.
[0080] method
[0081] In a second aspect, the present invention provides a method for treating a graphite starting material to produce a graphite material of the present invention having improved oxidation susceptibility and electrical resistance. In particular, a method for producing a graphite material is provided, wherein
[0082] a) subjecting the graphite starting material to a surface modification process comprising heating to a temperature of 300 to 1700° C. in the presence of an oxidizing process gas such as, but not limited to, oxygen, air, oxygen-enriched air, carbon dioxide, ozone, steam, NO x (including but not limited to NO 2 、NO、N 2 O) or any combination thereof; and
[0083] b) obtaining the graphite material of the present invention.
[0084] The present inventors have discovered that graphite materials with improved oxidation susceptibility and electrical resistance can be obtained by carefully selecting the starting materials and adjusting key process parameters such as residence time, oxidation process gas flow rate and temperature to obtain graphite materials characterized by the parameters described herein.
[0085] In a preferred embodiment, step a) comprises heating to a temperature of 500-1400°C, preferably 700-1100°C.
[0086] The graphite starting material may be natural graphite, synthetic graphite, expanded graphite or a mixture thereof.
[0087] The graphite starting material was not coated with a carbon coating.
[0088] Natural graphite is extracted from ores, where the typical content in the ore is 3-10% by weight. The ore is crushed and the graphite flakes are separated from the rock by flotation and centrifugation. The typical purity of the resulting graphite is 85-96% by weight. To obtain higher purity, the graphite can be chemically treated using a highly concentrated KOH solution followed by an acid treatment, which can include concentrated HCl, H 2 SO 4 The resulting graphite can be further ground to a desired particle size depending on the final application.
[0089] Synthetic graphite is prepared from natural or petroleum carbon precursors in a high temperature process that converts amorphous carbon into carbon of higher order structure. Synthetic graphite is usually produced by heat treating a precursor carbonaceous material in an Acheson furnace (as described in U.S. Pat. No. 933,944), where a high current flux is passed through the carbonaceous material between two electrodes. The material is heated by resistive heating (Joule effect) and thermal conduction at temperatures above 2000°C where graphitization occurs. Depending on the final application for the natural graphite, the resulting graphite is further ground to the desired particle size.
[0090] Expanded graphite is an exfoliated form of graphite. A method for producing expanded graphite is described, for example, in EP0981659B1. The production method is based on thermal exfoliation of graphite intercalation compounds, which are formed by treating graphite flakes with a strong acid in the presence of an oxidant such as a combination of highly concentrated sulfuric acid and nitric acid. The intercalated graphite is then subjected to a thermal shock by rapid heating to a temperature of about 850 to 1000°C, which causes the guest anions and acid molecules between the graphite layers to decompose into gaseous products that exfoliate the graphite layers. Alternatively, microwave radiation can be used for the exfoliation process. Finally, the graphite is ground, which further delaminates and separates the expanded graphite.
[0091] In a preferred embodiment, the starting graphite material is ground prior to being subjected to the surface modification treatment.
[0092] The starting graphite material may be a mixture of 10 to 90 wt% natural or synthetic graphite and 90 to 10 wt% expanded graphite. Increasing the amount of expanded graphite will increase the conductivity, however at a correspondingly higher material cost.
[0093] Oxidation is achieved by heating the graphite starting material in the presence of an oxidizing process gas such as, but not limited to, oxygen, air, oxygen-enriched air, carbon dioxide, ozone, steam, NO x (including but not limited to NO 2 、NO、N 2 In a preferred embodiment, the powder is treated in a high temperature furnace containing oxygen, CO 2, ozone, steam and / or NO x (including but not limited to NO 2 、NO、N 2 Oxidation is achieved by heating the graphite starting material for a specific time in the presence of at least one oxidizing process gas of at least one of the following: (i) 2) 3) 4) 5) 6) 7) 8) 9) 10) 11) 12) 13) 14) 15) 16) 17) 18) 19) 20) 21) 22) 23) 24) 25) 26) 27) 28) 29) 30) 31) 32) 33) 34) 35) 36) 37) 38) 39) 40) 41) 42) 43) 44) 45) 46) 47) 48) 48) 49) 50) 51) 52) 53) 54) 55) 56) 57) 58) 59) 60) 61) 62) 64) 65) 66) 67) 68) 69) 70) 71) 72) 73) 74) 75) 76) 77) 78) 79) 80) 81) 82) 84) 85) 86) 90) 87) 88) 91) 80) 81) 82) 84) 80) 91) 81) 82) 84) 85) 90) 81) 8
[0094] The oxidizing process gas used may be, but is not limited to, oxygen, air, oxygen-enriched air, carbon dioxide, ozone, steam, and NO x (including but not limited to NO 2 、NO、N 2 O). It should be understood that the oxidizing process gas may also be any combination of the above gases, optionally mixed with an inert carrier gas such as nitrogen or argon.
[0095] In a preferred embodiment, the oxidizing process gas used is air or CO 2 .
[0096] It is generally understood that with increasing oxygen concentration, ie higher oxygen partial pressure in the oxidation process gas, the oxidation process is faster. The amount of oxidation process gas depends on the amount of graphite starting material so as to maintain a certain C / O ratio to allow efficiency of the process.
[0097] The residence time in step a) required to obtain a graphite material characterized by specific properties as described herein will depend on the type of reactor selected, the process conditions (such as temperature, carbon amount and oxygen amount). In the case of a batch process, the residence time can be adapted to any time required to achieve the final properties of the graphite material described herein. In the case of a continuous process (e.g., rotary kiln, roller hearth kiln, etc.), it may be necessary to adjust process parameters such as temperature or carbon throughput according to the maximum possible residence time. For roller hearth kilns, this can exceed 5 hours (depending on the design). In a rotary kiln, a maximum residence time of several hours can be used.
[0098] In one embodiment, a batch process is used with a residence time of 30 to 120 minutes. In another embodiment, a continuous process is used with a residence time of 15 to 45 minutes. For both embodiments, it must be kept in mind that furnace design and carbon mass loading significantly affect process parameters.
[0099] Using different starting materials, temperatures and oxygen partial pressures may require adjustment of the processing time to obtain a graphite material having the desired parameters as defined herein.
[0100] The flow rate of the oxidation process gas depends on the size of the equipment. Those skilled in the art can adjust the flow rate according to the characteristics of the oxidation process gas, the treatment temperature and the residence time in the furnace to obtain the graphite material of the present invention.
[0101] Process Parameters The oxidized process gas to carbon ratio (kg / kg) is defined herein as the ratio of kg of oxidized process gas to kg of solid carbon. The term "solid carbon" refers to the elemental carbon contained in the graphite material to be treated. The oxidized process gas to carbon ratio depends strongly on the technology used and other process parameters such as residence time and temperature.
[0102] The ratio of oxidizing process gas to carbon is generally from 25 kg / kg to 0.005 kg / kg, preferably from 15 kg / kg to 0.01 kg / kg, more preferably from 5 kg / kg to 0.2 kg / kg.
[0103] If air is used as the oxidation process gas, the ratio of oxidation process gas to carbon is generally from 25 kg / kg to 0.02 kg / kg, preferably from 15 kg / kg to 0.04 kg / kg, more preferably from 10 kg / kg to 0.06 kg / kg.
[0104] If oxygen is used as the oxidizing process gas, the ratio of oxidizing process gas to carbon is generally from 5 kg / kg to 0.005 kg / kg, preferably from 3 kg / kg to 0.01 kg / kg, more preferably from 2 kg / kg to 0.02 kg / kg.
[0105] If steam is used as the oxidation process gas, the ratio of oxidation process gas to carbon is generally from 7 kg / kg to 0.005 kg / kg, preferably from 5 kg / kg to 0.01 kg / kg, more preferably from 3 kg / kg to 0.02 kg / kg.
[0106] If ozone is used as the oxidizing process gas, the ratio of oxidizing process gas to carbon is typically from 18 kg / kg to 0.015 kg / kg, preferably from 15 kg / kg to 0.02 kg / kg, more preferably from 10 kg / kg to 0.03 kg / kg.
[0107] If using CO 2 As the oxidation process gas, the ratio of the oxidation process gas to carbon is generally 20 kg / kg to 0.01 kg / kg, preferably 15 kg / kg to 0.02 kg / kg, more preferably 10 kg / kg to 0.05 kg / kg.
[0108] If you use NO 2 As the oxidation process gas, the ratio of the oxidation process gas to carbon is usually 8 kg / kg to 0.005 kg / kg, preferably 7 kg / kg to 0.01 kg / kg, more preferably 6 kg / kg to 0.02 kg / kg.
[0109] If you use N 2 O is used as the oxidizing process gas, then the ratio of oxidizing process gas to carbon is generally 16 kg / kg to 0.01 kg / kg, preferably 14 kg / kg to 0.02 kg / kg, more preferably 10 kg / kg to 0.04 kg / kg.
[0110] Other aspects
[0111] In a third aspect, the present invention provides a negative electrode or a positive electrode comprised in a battery, the battery comprising the graphite material of the present invention.
[0112] In a preferred embodiment, the electrode comprises a graphite material as a conductive additive.
[0113] As described herein, the use of graphite materials with low oxidation susceptibility and low electrical resistance in batteries or fuel cells has the benefits of extending battery or fuel cell life, slowing down battery or fuel cell efficiency degradation, and improving safety by reducing the risk of graphite decomposition into gas. In addition, lower electrical resistance will allow battery or fuel cell manufacturers to add less conductive additives, thereby achieving higher battery capacity.
[0114] In a fourth aspect, the present invention provides a battery comprising the graphite material of the present invention.
[0115] In a preferred embodiment, the battery comprises an electrode comprising a graphite material as a conductive additive.
[0116] The battery can be a lithium-ion battery, a lead-acid battery, an alkaline battery or a nickel-cadmium battery, preferably a lithium-ion battery.
[0117] In a preferred embodiment, the battery is a lithium ion battery or an alkaline battery and includes a positive electrode containing a graphite material as a conductive additive.
[0118] In a preferred embodiment, the battery is a lead-acid battery and includes a negative electrode containing a graphite material as a conductive additive.
[0119] In a fifth aspect, the present invention provides a fuel cell comprising the graphite material of the present invention.
[0120] In a sixth aspect, the present invention provides use of the graphite material of the present invention in any one of the following: a lithium ion battery, a lead-acid battery, an alkaline battery, a nickel-cadmium battery, and a fuel cell.
[0121] In a preferred embodiment, graphite material is used as the conductive additive.
[0122] In a preferred embodiment, the graphite material is used as a conductive additive in electrodes of lithium ion batteries.
[0123] In summary, the subject matter of the invention as described above advantageously allows optimizing oxidation susceptibility and electrical resistance in graphite materials.
[0124] It is intended that all matter contained in the above description be interpreted as illustrative rather than restrictive.Therefore, certain changes may be made to the above-mentioned compositions, uses and methods without departing from the scope of the invention.
[0125] The present invention will be further described by the following examples, which illustrate the preparation of graphite materials and their corresponding properties and do not limit the present invention.
[0126] Example
[0127] Measurement method
[0128] pH
[0129] 1 g of graphite powder was dispersed in 49 ml of distilled water with 2 drops of ethanol and measured by a pH meter with a calibrated pH electrode.
[0130] Scott density
[0131] Scott density was determined by passing dry carbon powder through a Scott volumeter according to ASTM B 329-98 (2003). The powder was collected in a 1 / 3 container (corresponding to 16.39 cm 3 ) and weighed accurately to 0.1 mg. The ratio of weight to volume corresponds to the Scott density. Three measurements must be made and the average calculated. The bulk density of graphite is calculated from the weight of a 250 ml sample in a calibrated glass measuring cylinder.
[0132] Raman analysis
[0133] Raman analysis was performed using a LabRAM-ARAMIS Micro-Raman spectrometer from HORIBA Scientific with a 632.8 nm HeNe LASER. The ratio ID / IG is based on the intensity ratio of the so-called band D and band G. These peaks are characteristic of carbon materials and are at 1350 cm -1 and 1580cm -1 Measured at.
[0134] Particle Size Distribution (PSD) by Laser Diffraction
[0135] The presence of particles in a coherent light beam causes diffraction. The size of the diffraction pattern is related to the particle size. A parallel light beam from a low-power laser illuminates a cell containing a sample suspended in water. The light beam leaving the cell is focused by an optical system. The distribution of the light energy in the focal plane of the system is then analyzed. The electrical signal provided by the optical detector is converted into a particle size distribution by a calculator. The method obtains the ratio of the total volume of particles to the discrete number of size categories that form a volume particle size distribution (PSD). The particle size distribution is defined by the values D10, D50 and D90, where 10% (by volume) of the particle population has a size below the D10 value, 50% (by volume) of the particle population has a size below the D50 value, and 90% (by volume) of the particle population has a size below the D90 value.
[0136] The particle size distribution data by laser diffraction cited herein have been measured with a MALVERN Mastersizer S. To determine the PSD, a small sample of the graphite material is mixed with a few drops of a wetting agent and a small amount of water. The sample prepared in the manner described is introduced into the storage container of the instrument (MALVERN Mastersizer S) and the measurement is carried out after 5 minutes of ultrasonic treatment at an intensity of 100% and a pump and stirrer speed set at 40%.
[0137] Reference: ISO 13320(2009) / ISO 14887
[0138] Oxygen concentration / oxygen content
[0139] The oxygen concentration in graphite materials is evaluated using the principle of inert gas fusion or solid carrier gas thermal extraction. The sample is placed in a graphite crucible and inserted into an electrode furnace. The crucible is held between the upper and lower electrodes of a pulse furnace. After purging with an inert gas (He or Ar), a high current is passed through the crucible, producing a temperature increase (above 2500°C). The gases produced in the furnace are released into the flowing inert gas stream. The gas stream is then sent to an appropriate infrared (O as CO, by NDIR) or thermal conductivity (N and H, by TCD) detector for measurement. The instrument is calibrated using known reference materials.
[0140] resistance
[0141] Use the following steps to measure resistance:
[0142] Volume resistivity can be measured by the following methods:
[0143] preparing a mixture containing 95% electrolytic manganese dioxide and 5% by weight of graphite (when synthetic or natural graphite is used as the graphite starting material) or 3% by weight of graphite and 97% electrolytic manganese dioxide (when expanded graphite is used as the graphite starting material);
[0144] 10 g of the resulting mixture was pressed at 180 Nm in a mold having a length of 50 mm and a width of 12 mm to obtain a block;
[0145] Measure the height (H) and width (W) of the block;
[0146] Measure bulk resistance (R) using a 4-point probe.
[0147] • Calculate the resistivity as H*R / D, where D is the distance of the probe measuring needle.
[0148] BET surface area
[0149] The method is based on measuring the absorption isotherm of liquid nitrogen in the range of p / p0=0.04-0.26 at 77K. Nitrogen adsorption is performed on Quantachrome Autosorb-1. According to the procedure proposed by Brunauer, Emmet and Teller (Adsorption of Gases in Multimolecular Layers, J.Am.Chem.Soc., 1938, 60, 309-SI9), the monolayer capacity can be determined. The specific surface area is then calculated based on the cross-sectional area of the nitrogen molecules, the monolayer capacity and the weight of the sample. The isotherms measured at 77K in the pressure range of p / p0=0.01-1 can be processed with DFT calculations to evaluate the pore size distribution, micropore and mesopore volume and area.
[0150] Reference: Ravikovitch, P., Vishnyakov, A., Russo, R., Neimark, A., Langmuir 16 (2000) 2311-2320; Jagiello, J., Thommes, M., Carbon 42 (2004) 1227-1232.
[0151] X-ray diffraction
[0152] X-ray diffraction (XRD) data were collected using a PANalytical X'Pert PRO diffractometer coupled to a PANalytical X'Celerator detector.
[0153] The instrument data and measurement parameters of the diffractometer used are listed in Table 1.
[0154] The instrument data and measurement parameters of XRD measurement are listed below:
[0155]
[0156] Data were analyzed using PANalytical X'Pert HighScore Plus software.
[0157] Interlayer spacing c / 2
[0158] The interlayer spacing c / 2 is determined by X-ray diffraction. The angular position of the maximum peak of the
[002] and
[004] reflection patterns is determined. The interlayer spacing is calculated by applying the Bragg equation (Klug and Alexander, X-ray diffraction Procedures, John Wiley & Sons Inc., New York, London (1967)). In order to avoid problems caused by the low absorption coefficient of carbon, instrument arrangement and non-planarity of the sample, internal standard silicon powder is added to the sample and the graphite peak position is recalculated based on the position of the silicon peak. The graphite sample is mixed with the silicon standard powder by adding a mixture of polyethylene glycol and ethanol. The resulting slurry is then applied to a glass plate by a scraper with a spacing of 150 μm and dried.
[0159] Crystallite size Lc
[0160] The crystallite size is determined by analyzing the
[002] and
[004] diffraction patterns and determining the width of the peak at half maximum. The broadening of the peak should be affected by the crystallite size proposed by Scherrer (P.Scherrer, Nachrichten 2, 98 (1918)). However, the broadening is also affected by other factors such as X-ray absorption, Lorentz polarization and atomic scattering factors. Several methods have been proposed to take these effects into account by using an internal silicon standard and applying the calibration function to the Scherrer equation. For the present invention, the method proposed by Iwashita is used (N. Iwashita, C. Rae Park, H. Fujimoto, M. Shiraishi and M. Inagaki, Carbon 42, 701-714 (2004)). The sample preparation is the same as for the c / 2 determination described above.
[0161] Ash content
[0162] The ash content is evaluated by weight loss. A low-walled ceramic crucible is heated to 800°C in a muffle furnace and cooled to room temperature in a desiccator. 10 g of dry powder sample is weighed in a low-walled ceramic crucible (accuracy 0.1 mg). The powder is burned at a temperature of 810°C (at least 8 hours) until constant weight is reached. The residue corresponds to the ash content and is reported as a percentage of the initial weight of the sample.
[0163] Reference: ASTM C561 Standard Test Method for Ash in Graphite Samples.
[0164] Example 1
[0165] In a rotary furnace or a continuously stirred reactor, air or CO 2 The different graphite starting materials were processed at temperatures between 600-900°C.
[0166] The processing conditions used to prepare the different graphite materials are described in Table 1.
[0167]
[0168] The pH, Scott density, Raman D / G intensity ratio and various other parameters of the obtained graphite material were measured (Table 2). In addition, the oxidation susceptibility and electrical resistance of the material were determined.
[0169] The same set of measurements were performed on the starting materials before treatment and for other comparative examples. The results are shown in Tables 3 and 4.
[0170] By comparing the data it can be seen that the material having the claimed combination of parameters has an improved balance of low oxidation susceptibility and low electrical resistance.
[0171]
[0172]
[0173]
Claims
1. A graphite material having the following properties: a) a pH of at least 5.4 as described herein; b) a Scott density less than or equal to 0.11 g / cm 3 ;as well as c) When measured with a laser having an excitation wavelength of 632.8 nm, the Raman D / G intensity ratio is 0.220 to 0.
420.
2. The graphite material according to claim 1, wherein the pH is 5.4-12, preferably 5.4-11, or 5.4-10.
3. The graphite material according to claim 1 or 2, wherein the Scott density is less than or equal to 0.10 g / cm 3 , preferably less than or equal to 0.09 g / cm 3 .
4. The graphite material according to any one of claims 1 to 3, wherein the Raman D / G intensity ratio is 0.23 to 0.
40.
5. The graphite material according to any one of claims 1 to 4, further having at least one of the following properties: d) a D90 of at least 11.0 μm as measured by laser diffraction; e) an oxygen concentration of at least 0.042 wt % based on the total weight of the graphite material as measured by elemental analysis.
6. The graphite material of any one of claims 1-5, wherein D90 measured as described herein is at least 5 μm.
7. The graphite material of any one of claims 1 to 6, wherein the oxygen concentration is at most 1.0 wt%, or at most 0.9 wt%, or at most 0.7 wt%, or at most 0.6 wt%, or at most 0.5 wt%.
8. The graphite material of any one of claims 1 to 7, further having a thickness of at least 5.5 m / s as measured herein. 2 / g BET specific surface area.
9. The graphite material according to any one of claims 1 to 8, further comprising: i) an oxidizability of less than or equal to 0.19, measured as described herein; and ii) a resistance less than or equal to 600 mΩ·cm, preferably 400 mΩ·cm, most preferably 285 mΩ·cm, measured as described herein.
10. The graphite material of claim 9, wherein: i) the oxidizability is less than or equal to 0.18, or 0.17, or 0.16, or 0.15; and / or ii) the resistance is less than or equal to 260 mΩ·cm, or less than or equal to 255 mΩ·cm, or less than or equal to 250 mΩ·cm.
11. A method for producing a graphite material according to any one of claims 1 to 10, wherein the graphite starting material is subjected to a surface modification process comprising heating to a temperature of 300 to 1700°C in the presence of an oxidizing process gas such as, but not limited to, oxygen, air, oxygen-enriched air, carbon dioxide, ozone, steam, NO x (including but not limited to NO2, NO, N2O) or any combination thereof.
12. The method of claim 11, wherein the ratio of the oxidizing process gas to carbon in graphite is 25 kg / kg to 0.005 kg / kg.
13. The method of claim 11 or 12, wherein step a) comprises heating to a temperature of 500-1400°C, preferably 700-1100°C.
14. A negative electrode or positive electrode contained in a battery, comprising the graphite material according to any one of claims 1 to 10, preferably as a conductive additive.
15. A battery comprising the graphite material according to any one of claims 1 to 10, wherein the battery is preferably a lithium ion battery, a lead acid battery, an alkaline battery or a nickel cadmium battery.
16. A fuel cell comprising the graphite material according to any one of claims 1 to 10.
17. Use of the graphite material according to any one of claims 1 to 10 in any one of the following: lithium-ion batteries, lead-acid batteries, alkaline batteries, nickel-cadmium batteries, and fuel cells.
